Performance of uplink feedback MIMO system using joint transmitter-receiver and polarization-multiplexing. (July 2016) - Nagaradjane, Prabagarane; Muthu, Tamilarasi
Highlights: SER and capacity performance of a uplink-feedback MIMO system is studied under. Perfect-CIRs based joint Tx-Rx design with polarization-multiplexing-ideal feedback. Quantized-CIRs aided joint Tx-Rx with polarization-multiplexing-noisy feedback. Quantized-CIRs based joint Tx-Rx with polarization-multiplexing-fading feedback. Quantized-CIRs assisted joint Tx-Rx with polarization-multiplexing-delayed feedback. Graphical abstract: Abstract: In this paper, we consider the performance of a cellular uplink (UL) multi-user feedback multiple-input multiple-output (MIMO) system assisted by joint transmitter-receiver (Tx-Rx) design and polarization-multiplexing (PM). PM is realized with the aid of dual and triply-polarized antennas. At the transmitter, we take advantage of only the individual user's channel impulse responses (CIRs) obtained through feedback channels that endure noise, fading and delay to construct the preprocessing matrix, while at the receiver the post-processing matrix construction relies on the perfect CIRs of all the users. In multi-user UL-MIMO transmissions, multiple-access interference (MAI) and inter-antenna interference (IAI) can severely degrade the system's performance. Our study shows that the joint Tx-Rx is capable of completely eliminating the IAI as well as the MAI when it employs perfect CIRs based preprocessing and post-processing. On the other hand, noise, fading and delay tainted quantized-CIRs based preprocessing results in noticeable performance degradation due to imperfect removal of IAI. Nevertheless, our results demonstrate that, when the preprocessing is based on the quantized-CIRs obtained through ideal feedback channels, the resultant achievable symbol-error-rate and sum-capacity remain close to that obtained with the perfect CIRs based design.